La comunicación familiar y las actitudes hacia el consumo de alcohol y drogas en los estudiantes de segundo año de bachillerato paralelo c, de la Unidad Educativa Marieta de Veintimilla, año lectivo 2020-2021. - Medina Ríos, Eliana Lucrecia (2022)
The present study called FAMILY COMMUNICATION AND ATTITUDES TOWARDS ALCOHOL AND DRUG USE IN SECOND YEAR STUDENTS OF THE PARALLEL BACCALAUREATE C, OF THE MARIETA EDUCATIONAL UNIT OF TWENTY-MILE, SCHOOL YEAR 2020-2021. , aimed at establishing the relationship between family communication and attitudes towards alcohol and drug use in second-year students in parallel baccalaureate C; quantitative study, descriptive, non-experimental and cross-sectional design. The Parent-Child/Ace Communication Scale (CA-M/CAP) of Barnés and Olson (1982) and the Attitude to Alcohol Consumption Scale (OMS) were applied to the sample of 20 students. In the results obtained on family communication, it was found that 90% maintain a medium level of offensive communication within the home and, with respect to the attitudes towards alcohol consumption of those investigated, it was found that attitudes towards alcohol abuse are at a high level with 35% for favorable attitudes. It is concluded that a large percentage of the students maintain an offensive family communication, while a substantial percentage show attitudes favoring alcohol and drug abuse, these attitudes being worrisome for the age range of those investigated. It is recommended the DECE and parents carry out psycho-educational activities with the students to strengthen intra-family ties and increase attitudes towards non-consumption of alcohol and drugs. Key words: attitudes, alcohol, family communication, consumption, drugs.